Current Issues of Protection of State Sovereignty of Ukraine in the Context of Globalization - Melnykova, Dariia (Journal of Legal Studies, 2021)
The relevance of the research topic is based on modern rapid European integration trends in Ukraine and the definition of one of the main vectors of foreign policy accession to the European Union, among the prospects of which is the need to protect Ukraine’s state sovereignty. The purpose of the article is to study the essence of sovereignty in the modern world and the relevance of the protection of state sovereignty on the example of Ukraine. The paper reveals the essence of sovereignty in the context of globalization of society. Along with this, the article analyzes the main trends in the formation of state sovereignty on the example of Ukraine. Also, it determines the main characteristics of state sovereignty in terms of integration. Finally, the paper reveals the content of the main integration vectors of Ukraine and their impact on state sovereignty. The scientific novelty of this study lies in the innovative understanding and justification of the essence, feasibility and necessity of protecting the state sovereignty of Ukraine during integration processes. The author proposes to improve the legal regulation of the prospects of Ukraine’s integration, based on the elaborated works of domestic and foreign researchers and her own vision of the problem.